Relative deficiency in interferon-γ-secreting CD4+ T cells is strongly associated with poorer COVID-19 vaccination responses in older adults - Ho, Vanda W. T. (2024)
Although the two-dose mRNA vaccination regime provides protection against SARS-CoV-2, older adults have been shown to exhibit poorer vaccination responses. In addition, the role of vaccine-induced T-cell responses is not well characterised. We aim to assess the impact of age on immune responses after two doses of the BNT162b2 mRNA vaccine, focussing on antigen-specific T-cells. A prospective 3-month study was conducted on 15 young (median age 31 years, interquartile range (IQR) 25-35 years) and 14 older adults (median age 72 years, IQR 70-73 years). We assessed functional, neutralising antibody responses against SARS-CoV-2 variants using ACE-2 inhibition assays, and changes in B and T-cell subsets by high-dimensional flow cytometry. Antigen-specific T-cell responses were also quantified by intracellular cytokine staining and flow cytometry. Older adults had attenuated T-helper (Th) response to vaccination, which was associated with weaker antibody responses and decreased SARS-CoV-2 neutralisation. Antigen-specific interferon-γ (IFNγ)-secreting CD4+ T-cells to wild-type and Omicron antigens increased in young adults, which was strongly positively correlated with their neutralising antibody responses. Conversely, this relationship was negative in older adults. Hence, older adults' relative IFNγ-secreting CD4+ T cell deficiency might explain their poorer COVID-19 vaccination responses. Further exploration into the aetiology is needed and would be integral in developing novel vaccination strategies and improving infection outcomes in older adults.